2018
DOI: 10.4028/www.scientific.net/msf.931.974
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Assessment of Sludge Biocenosis while Nitrogen Removal

Abstract: The paper presents the results of studies on increasing the efficiency of wastewater treatment from nitrogen compounds during the re-engineering of sludge bioreactors with the use of contact carriers for biomass immobilization. To assess the contribution of the indicative species of microorganisms involved in the processes of nitrification and denitrification, an analysis of the indices of species diversity by functional zones was carried out. The results of the operation of the bioreactor are given when using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…X-ray phase analysis (Fig. 6) [17] showed that carbide sludge contains phases: calcium carbonates (CaCO3) and magnesium (MgCO3), which allows it to be used as a reagent instead of quicklime, and its lower cost (5 times) causes a reduction in costs [18][19][20][21]. Trial coagulation was also carried out using aluminum-containing sludge, which is a large-tonnage waste that is formed during alkaline milling of aluminum structures and contains mainly sodium hydroaluminate (70-75%), pH about 13. with the main component (up to 50%) in the form of sodium hydroaluminate (SHA) ) [7].…”
Section: Discussionmentioning
confidence: 99%
“…X-ray phase analysis (Fig. 6) [17] showed that carbide sludge contains phases: calcium carbonates (CaCO3) and magnesium (MgCO3), which allows it to be used as a reagent instead of quicklime, and its lower cost (5 times) causes a reduction in costs [18][19][20][21]. Trial coagulation was also carried out using aluminum-containing sludge, which is a large-tonnage waste that is formed during alkaline milling of aluminum structures and contains mainly sodium hydroaluminate (70-75%), pH about 13. with the main component (up to 50%) in the form of sodium hydroaluminate (SHA) ) [7].…”
Section: Discussionmentioning
confidence: 99%